Training on Establishing Climate-Smart Villages (CSVs) in Myanmar to Improve Food Security and Resilience in Agriculture - Barbon, Wilson John; Myae, Chan; Bayot, Ruvicyn S.; Gonsalves, Julian Francis (2019)
This training on establish Climate-Smart Villages (CSVs) in Myanmar was a collaborative effort of the Food Security Working Group (FSWG) and the Myanmar Program of the International Institute of Rural Reconstruction. This was supported in part by donors of the FSWG and the International Development Research Center-Canada through the 3-year action research project of IIRR-Myanmar in 4 CSVs. The overall goal of this training was to increase the understanding of the concepts, processes and tools in implementing of CSVs as an approach to build climate resilience among small-holder farmers, achieve nutrition security and gender equality in Myanmar. It was aimed for local NGOs and members of the Food Security Working Group (FSWG), Myanmar’s largest alliance of development organizations advocating for food security and sustainable livelihoods in Myanmar. This training was part of IIRR-Myanmar’s out-scaling pathway by engaging and building capacities of local civil societies to replicate the CSV approach as platforms to promote climate smart agriculture in Myanmar.